Capability based- approach: Re-Invent people and materials viable relationships (ModaPalavra e-periódico, 2022)
Sustainability as an approach to the contemporary textile and fashion design; not only linked to the environmental vision but concerning the economy, respect for people's work and production. “A new dominant social paradigm (DSP) would focus on creating apparel products that are more efficient in material use, production and consumer utility, as well as better meeting the human needs of the consumer base, inherently more social than material needs. Similarly, clothing education in the dominant new social paradigm would promote the development of skills that would most likely include understanding human needs and ecosystem limitations, working collaboratively with the market rather than trying to dominate it and an understanding of local culture and tradition " (LeHew, 2011).
Keywords: new economy; materials relationships; surplus waste